Intermedicality in official health contexts: Use of medicinal plants by the inhabitants of a city in Argentinean Patagonia - Ferreras, Irene (2022)
The aim of this study was to explore how the use of medicinal plants and biomedical resources varies over time among patients attending primary health-care centers in Esquel city (Argentinean Patagonia) as related to socio-cultural and environmental variables. Interviews were carried out with 79 patients and information was analyzed using ethnobotanical techniques. Seventy-six percent of informants said they use medicinal plants and drugs in a complementary manner. They were mostly youths of urban origin. Gastrointestinal disorders are mostly treated through this strategy, exotic plants being the most commonly used ones, together with analgesics and synthetic digestives. Conversely, elderly people of rural origin kept cultural rules that restrict the combined use of plants and drugs to some etiologies. These informants claim to use drugs to treat complex diseases such as diabetes, thyroidism, etc. Health centers are intermedicality spaces where rural and urban memories reactivate, and where therapeutic responses diversify among social segments.